Parental stress and children's game addiction: a brief overview / Yong Azrina Ali Akbar, Wan Shahrul Aziah Wan Mahamad and Ramli Saad - Ali Akbar, Yong Azrina; Wan Mahamad, Wan Shahrul Aziah; Saad, Ramli (Universiti Teknologi MARA, Kedah, 2023)
Concerns about the potential negative effects on children's well-being have been sparked by the advancement of technology and the growing popularity of video games. Parental stress has been identified as a significant factor that can influence the behavior and development of children. This paper briefly overviews the relationship between parental stress and children's video game addiction, shedding light on the connection and potential interventional implications.